Macedonian Early Childhood Intervention: Challenges and Opportunities - Dimitrova Radojichikj, Daniela; Dukovska, Valentina (Armenian State Pedagogical University after Khacatur Abovyan, 2025)
Early childhood intervention is vital in supporting the development of children with disabilities or those at risk of developmental delays. Despite its well-known benefits, Macedonian Early Childhood Intervention services still encounter significant challenges. This study included 33 ECI professionals nationwide, who participated in six focus group discussions. The focus groups addressed the daily obstacles these professionals encounter - from screening procedures to parental involvement in Early childhood intervention services. Participants highlighted the lack of standardized Early childhood intervention protocols, the need for ongoing training, and greater financial support from the state.